Analysis of the Role of BPK RI in Promoting Organizational Capacity Development of ASEANSAI in the Period 2018-2023 - Annisa, Izzah; Sampurna, Agung Firman (Syntax Literate, 2024)
The development of international audit organizations is crucial for enhancing accountability, transparency, and integration of public sector financial management globally. In Southeast Asia, the establishment of the Association of Southeast Asian Nations Supreme Audit Institutions (ASEANSAI) is significant for fostering regional cooperation in financial auditing. The Supreme Audit Agency of the Republic of Indonesia (BPK RI) plays a pivotal role as the ASEANSAI Secretariat, supporting and developing the organization's performance. As ASEANSAI matures, organizational capacity development becomes a key challenge. This study aims to analyze BPK RI's role in enhancing ASEANSAI's organizational capacity during the 2018-2023 period, utilizing Dillen et al.'s (2019) theory of transition from managerial roles to strategic experts and Walters' (2019) theory of organizational capacity development. Employing a qualitative methodology and conducting in-depth semi-structured interviews with 18 individuals from both internal and external ASEANSAI, the study identified several suboptimal aspects in the Secretariat's role and ASEANSAI's capacity development, including human resource management, financial management, and organizational performance stability. The findings suggest that these issues stem from inadequate strategic human resource development, limited financial resources, and external environmental changes such as the COVID-19 pandemic and regional socio-humanitarian issues.